PROSES PENILAIAN DOMAIN SUMBERDAYA IKAN, HABITAN DAN EKOSISTEM, DAN TEKNOLOGI PENANGKAPAN IKAN DALAM PENDUGAAN PEFORMA PERIKANAN DI TAMAN WISATA ALAM LAUT TELUK KUPANG - Alexander S Tanody; Ida Ayu Lochana Dewi; Naharuddin Sri (Partner, 2019)
The evaluation of fisheries performance using Ecosystem Approach to Fisheries Management (EAFM) is done by evaluating indicators based on existing data. The data used for indicators’ evaluation have to be up to standards and requirements in place. Three out of six domains that are going to be evaluated in this process consist of fish resources, habitats and ecosystems of fish, and also the catching technology of it. The process of evaluating the fisheries performance of Kupang Bay Marine Nature Park has been finished. This research is made to help describe fisheries performance that would be a great consideration for development of sustainable fisheries in collaboration with development of tourism inside the area. Based on results of composite evaluation and analysis, fisheries performance in Kupang Bay Marine Nature Park is categorized as not applying the EAFM enough. This is not only because the real condition on the field is very unsatisfactory, even gradually diminishing, but also because the availability of data needed for research has not been met. In order to guarantee the validity of fisheries performance in the area for the next two years, there are some strategic actions being offered like provision of institution that will manage data integration, formation of observers that will accompany fishermen during fish catching, training for fishermen so they can do data collecting during fish catching, development of integrated research programs, and optimization of fish auction places in relation to data recording for performance evaluation. Active involvement of all parties will hopefully guarantee the improvement of fisheries performance in the next two years.